Scale-Up Cultivation of the Dinoflagellate Durusdinium glynnii Under Varying Inoculum Percentages: Effects on Growth Performance and Fatty Acid Profile - Pedro Rodrigues de Sena; Maria Eunice S. S. Lira; Deyvid Willame S. Oliveira; Barbara de Cassia S. Brandão; Jessika L. de Abreu; Watson Arantes Gama; Evando S. Araújo; Giustino Tribuzi; Alfredo O. Gálvez; Carlos Yure B. Oliveira (Phycology)
Microalgae are photosynthetic organisms with rapid growth and high biochemical diversity, capable of thriving in a variety of environments. Among them, dinoflagellates, particularly symbiotic species like Durusdinium glynnii, have gained attention due to their potential for biotechnological applications, especially in the production of valuable fatty acids. However, the delicate cultivation of dinoflagellates remains a challenge due to their sensitivity to shear stress and complex morphology. In this study, we evaluated the influence of inoculum percentage (10%, 25%, and 50%) on the growth performance and fatty acid profile of D. glynnii during a scale-up process from test tubes to a pilot-scale photobioreactor. Higher inoculum concentrations (50%) promoted faster acclimatization, higher specific growth rates (µmax), and greater final biomass densities, optimizing the cultivation process. Meanwhile, lower inoculum concentrations (10%) favored the accumulation of polyunsaturated fatty acids, particularly DHA (C22:6n3), indicating a trade-off between biomass productivity and fatty acid biosynthesis. Overall, D. glynnii demonstrated robust adaptability, reinforcing its potential as a sustainable source of bioactive compounds. Further studies focusing on cellular and metabolic pathways are needed to better elucidate the mechanisms underlying lipid production and growth in this promising species.